2000
DOI: 10.1037/0022-0663.92.4.659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preschool phoneme identity training after six years: Outcome level distinguished from rate of response.

Abstract: Grade 5 children who had been trained in phoneme identity 6 years earlier in preschool were superior to untrained controls on irregular word reading; on a composite list of nonwords, regular words, and irregular words; and on a separate nonword test. Some of the trained children had become poor readers by Grade 5. These poor readers had made slow progress in achieving phonemic awareness in preschool even though they were eventually successful. In general, the rate at which trained children achieved phonemic aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 27 publications
(50 reference statements)
7
120
0
6
Order By: Relevance
“…It is thus difficult to measure growth in phonological awareness, and this is a major problem for the identification of children who are at risk for reading problems and/or dyslexia. Several studies have shown that the measurement of phonological awareness and growth in this capacity are critical for the early identification of reading problems (Byrne, Fielding-Barnsley, & Ashley, 2000;Hindson et al, 2005;Spector, 1992). Growth in phonological awareness appeared to account for variance in reading in addition to that accounted for by the actual level of phonological awareness ability.…”
Section: Problems With the Measurement Of Phonological Awarenessmentioning
confidence: 99%
“…It is thus difficult to measure growth in phonological awareness, and this is a major problem for the identification of children who are at risk for reading problems and/or dyslexia. Several studies have shown that the measurement of phonological awareness and growth in this capacity are critical for the early identification of reading problems (Byrne, Fielding-Barnsley, & Ashley, 2000;Hindson et al, 2005;Spector, 1992). Growth in phonological awareness appeared to account for variance in reading in addition to that accounted for by the actual level of phonological awareness ability.…”
Section: Problems With the Measurement Of Phonological Awarenessmentioning
confidence: 99%
“…That is, the ability to analyze, synthesize and manipulate phonemes and syllables must be mastered in order for a child to adequately learn precisely how these sounds correspond to the arbitrarily defined shapes known as letters. Empirical evidence for this has come from the fact that preliterate children who have better PA skills are in turn quicker to learn to read (Wagner & Torgesen, 1987), and that both the absolute level (Share, Jorm, MacLean, & Mathews, 1984) and rate of acquisition (Byrne, Fielding-Barnesley, & Ashley, 2000) of early PA skills are excellent predictors of elementary reading skills. Wagner et al (1997) found that individual differences in PA persisted in explaining reading abilities each year from kindergarten through fourth grade, whereas the relationships between reading and other skills faded with development.…”
mentioning
confidence: 99%
“…Structured interventions during the preschool period have a significant impact on later reading acquisition. Randomized controlled trials have demonstrated unequivocally that language stimulation, interactive reading, explicit teaching of letter sounds and phonological awareness interventions, administered in daycare and kindergarten classrooms, can improve language and phonological awareness abilities in the short term and lead to improved reading outcomes over the long term (37)(38)(39)(40). Furthermore, it has been shown that interventions for at-risk children are most effective when they begin during infancy (41).…”
Section: Interventionsmentioning
confidence: 99%